Affective-Experiential Strategies in Learning Psycho-Dynamically Oriented Family Counseling - Campo Redondo, María (Omnia)
In this report, a look is offered to consider sorne of the pressing implications involved in teaching psycho-dynarnically oriented family counseling. The paper describes an experience which took place involving graduate students in a counseling prograrn. A family counseling course was designed and carried out in which didactic (cognitive) and affective (experiential) dirnensions were included. Qn the one hand, the fact that students had a working vision of the main theoretic concepts of dynamic family counseling was assured. On the other hand, affective-experiential strategies were introduced to help students recognize and use their emotional self-exploration and self-awareness when working with their family clients. The results of this experience show that students rnanifested an openness for taking into account their self-knowledge and self-consciousness when working with families. In addition, it was found that the participants reported an increase in the use of those feelings aroused in the sessions an empathic thermometer”™ to closely monitor what emotionally happens in a given family case.